A single-phase simplified DC-AC converter using DC-link capacitors and an H-bridge - Sai Divya Sindhura Nunna; Akhilesh Ketha; Srivastav Sai Goud Padamat; K. Rambabu; Ujwala Anil Kshirsagar; Abhilash Tirupathi (Institute of Advanced Engineering and Science, 2021)
This paper introduces a simplified inverter circuit using a single dc source and an H-bridge with a least possible number of “switching devices”. This topology does not employ multiple “dc sources”, which enhances the reliability of the configuration. The topology consists of two parts, namely: “Level generation parts” as well as “Polarity generation parts”, it is the mixture of some of the switching devices, DC-link capacitor and a single DC source completes the part of level generation. The H-bridge in the proposed structure produces the polarity generation part. A detailed explanation of the modulation system and operating modes of the proposed framework are discussed. Finally, in the MATLAB/SIMULINK platform, the projected network topology is simulated and the outcomes are presented.